Factors Affecting the Effectiveness of Internal Control in the Government Sector Perception of Employees at the Office Sukorejo Village, Gondanglegi District, Malang - Erin Hartutik (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Village Government is the Village Head or what is referred to by another name, assisted by Village apparatus as an element of village administration. In Law Number 6 of 2014 Concerning Villages explicitly assigns tasks to the village government, namely administering government, implementation, development, community development, and community empowerment based on Pancasila, the 1945 Constitution of the Republic of Indonesia, and Bhinneka Tunggal Ika. With the basic aim of protecting the entire Indonesian nation and all of Indonesia's bloodshed, promoting public welfare, educating the nation's life, and participating in carrying out world order based on freedom, eternal peace, and social justice. The importance of quality for village government officials in the implementation of governance and development. the results of the study show that mental attitude factors, discipline factors, education factors in the service sector will also determine the implementation of tasks for each village government apparatus.